ENDOTHELIAL DYSFUNCTION AND DERANGED LEVEL OF ASYMMETRIC DIMETHYL ARGININE IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Tariq, Kalsoom; Khan, Mudasser Ahmad (Journal of Postgraduate Medical Institute, 2015)
Objective: To determine the serum Asymmetric dimethyl arginine (ADMA) level, association of various biochemical parameters with plasma ADMA level in type 2 diabetic patients and also to compare with normal healthy individ -uals. Methodology: Analytical cross sectional study was conducted at Medical and Cardiology Departments of Khyber Teaching Hospital (KTH) and Hayatabad Medical Complex (HMC), Peshawar for a period of one year. A total of 140 participants with age range of 35-65 years, were divided into two groups. Blood was obtained from each participant for biochemical analysis. All data obtained was entered in SPSS version 15. A P-value of < 0.05 was considered as statistically significant. Results: An elevated ADMA was noted group B. In group A significant posi -tive correlation was observed between serum ADMA with TC and TG level and a non-significant correlation was observed between ADMA and HDL level. In case of group B a significant strong positive linear relationship was seen between ADMA level and different parameters like FBG, HbA1c, LDL and no significant correlation was seen between ADMA with TG and TC. Conclusion: Our study reveals increased serum ADMA levels in the patients suffering from type 2 diabetes mellitus without CAD when compared with the control group. Also a significant positive correlation was seen between serum ADMA level and FBS, HbA1c, TC, HDL-C and TG levels among the subjects of group B.